Marketing Communication Menggunakan Augmented Reality pada Mobile Platform - Julio Christian Young (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2015)
Augmented Reality is a technology that can project objects from the virtual world to the real world. Augmented Reality continues to be developed so it can be easy to implement into various devices. However, the device must have a camera, VGA card, and the ability to process data that is high enough to be able to process and projecting graphical data that captured by the camera and displayed to the screen. Marker-based Augmented Reality is still better than Markerless Augmented Reality due to several issues such as disturbances in the geomagnetic sensor that is used to map the Y axis and Z device that belongs to the user.